2016
DOI: 10.2320/matertrans.m2015439
|View full text |Cite
|
Sign up to set email alerts
|

System and Experiment on Fast Testing Vermicular Graphite Percent in Cast Iron Based on Ultrasonic Longitudinal Wave

Abstract: Vermicular graphite percent is an important index of evaluating the vermiculation of graphite in cast iron. Quantitative metallographic method is commonly used to test the vermicular graphite percent, but it can only detect certain parts of the cast iron specimen. Therefore, an ultrasonic system was designed to detect the degree of the vermiculation in cast iron according to the relationship between the ultrasonic propagation velocity and the vermicular graphite percent, and it is composed of the sink lled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Material of the micro cracks under different loading showed different growth trends, eventually lead to fracture. Ultrasonic testing has been applied in non-destructive testing of revolved workpieces [3][4][5][6][7][8][9]. Among these, the frame scan attached to the rotary shaft is the main form of detection and the parts that need to be tested are usually solid axes or pipe fittings with little change in diameter [10].…”
Section: Introductionmentioning
confidence: 99%
“…Material of the micro cracks under different loading showed different growth trends, eventually lead to fracture. Ultrasonic testing has been applied in non-destructive testing of revolved workpieces [3][4][5][6][7][8][9]. Among these, the frame scan attached to the rotary shaft is the main form of detection and the parts that need to be tested are usually solid axes or pipe fittings with little change in diameter [10].…”
Section: Introductionmentioning
confidence: 99%
“…Vermicularity is one of the most important parameters for evaluating vermicular graphite cast iron. Generally, the vermicularity must be higher than 80% [7]. However, because the residual magnesium content of qualified vermicular graphite cast iron is only 0.01-0.018%, the narrow range makes the production process relatively complex [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the ultrasonic characteristics of cast irons with different nodularities and matrix structures were reported by Collins et al [5]. Similarly, it was found that UT could be used to characterize the percent of vermicular graphite [6]. Besides, ultrasound is commonly used for defect detection, affording good sensitivity and penetration.…”
Section: Introductionmentioning
confidence: 99%